Unstable Elbow Dislocation with lpsilateral Distal Radius Fracture: A Rare Combination of Fracture Dislocation - KC, Kapil Mani; Pangeni, Bandhu Ram; Sigdel, Arun; Marhatta, Suman Babu (Nepal Orthopaedic Association Journal, 2016)
Elbow dislocation with coronoid process fracture and bony avulsion oflateral collateral ligament is an unstable type of dislocation. An associated distal radius fracture is a rare type of injury which increases the probability of the distal radius fracture being missed by the attending orthopaedic surgeon. We report a 54 year old male patient with this type of injury whose dislocated elbow joint was reduced and stabilized with an ulno-humeral K wire, and the distal radius fracture was reduced and fixed with multiple K wires. The ulno-humeral K wire was removed at three weeks while K wires in distal radius were removed after six weeks. The range of motion of both elbow and wrist joint was nearly normal, except for 15 degrees of FFD at the elbow joint six months after the surgical intervention.